Hip strength in collegiate female athletes with patellofemoral pain - Cichanowski, H. R.; Schmitt, J. S.; Johnson, R. J.; Niemuth, P. E. (Medicine & Science in Sports & Exercise, 2007)
Purpose: Decreased hip strength has been theorized to contribute to the development of patellofemoral pain. The purpose of this study was to test for strength differences of six hip muscle groups in collegiate female athletes diagnosed with unilateral patellofemoral pain compared with the unaffected leg and noninjured sport-matched controls.